Liberia rising? Foreign direct investment, persistent inequalities and political tensions. (1st September 2016) - Paczynska, Agnieszka
Abstract: A key component of post-conflict reconstruction is inclusive and equitable economic development. In the post-Cold War era, Western donors have promoted the liberal peacebuilding model that emphasises democratisation and marketisation to accomplish stability and development. Attracting Foreign Direct Investment is an essential component of these marketisation policies, contributing to creating new employment opportunities, bringing in new technologies, skills and access to international markets. Others point to potential negative consequences for social stability of large international firms entering post-civil war countries, creating winners and losers and contributing to conflicts over access to land, jobs, social services and revenues generated by the companies. This paper examines the socio-economic and political consequences of FDI flows in Liberia. It argues that the very success of encouraging FDI, mostly channelled into palm oil, forestry, rubber and iron ore mining, undermined other policy goals, and in particular poverty reduction strategies, contributing to an increase in political tensions and protests in the project-affected communities.